PELATIHAN REMAJA SIAGA PEDULI BENCANA TINGKAT DASAR TERINTEGRASI PADA EKTRA KURIKULER PRAMUKA DI SEKOLAH MENENGAH PERTAMA ISLAM TERPADU TUNAS CENDIKIA BATURAJA - Ni Ketut Sujati; M. Agung Akbar; Supangat Supangat (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Emergency conditions occur at unexpected times and places and require fast and appropriate handling. The reality is that it is rare for parents to pay attention to emergency response competency education, as in schools it has not been a concern. This community service aims to provide education through training on basic level disaster preparedness, to foster the character of Cadres of Caring Schools and Disaster Preparedness. Community service activities are carried out from August to November 2022 at the Tunas Cendekia Integrated Islamic School. The implementation is carried out every Saturday throughout the semester in scout extracurricular lessons. This activity resulted in the formation of disaster preparedness youth cadres (pen tie) as an effort to develop helpful skills so that during junior high school it was appropriate to start educating skills to become disaster preparedness youth cadres